2019
DOI: 10.1186/s12881-019-0861-4
|View full text |Cite
|
Sign up to set email alerts
|

Weak association between the interleukin-8 rs4073 polymorphism and acute pancreatitis: a cumulative meta-analysis

Abstract: Background Several studies have been performed to investigate the associations between interleukin (IL)-8 rs4073 polymorphism and acute pancreatitis (AP), but the results are inconclusive. We conducted this cumulative meta-analysis for a precise estimate of the relationship between IL-8 rs4073 polymorphism and acute pancreatitis. Methods We searched the electronic databases for relevant studies. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Secondly, emerging studies have shown that pancreatitis and IBD are diseases of immune dysregulation. Cytokine abnormalities, such as elevation of interleukin 1 β (IL-1 β ), IL-6, IL-8, and IL-10, are involved in pancreatitis and IBD [ 32 34 ]. Pancreatic tissue and gastrointestinal epithelial cells may share vulnerable cellular structures or target molecules [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, emerging studies have shown that pancreatitis and IBD are diseases of immune dysregulation. Cytokine abnormalities, such as elevation of interleukin 1 β (IL-1 β ), IL-6, IL-8, and IL-10, are involved in pancreatitis and IBD [ 32 34 ]. Pancreatic tissue and gastrointestinal epithelial cells may share vulnerable cellular structures or target molecules [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among all the cytokines, IL-8 stands out in the AP pathophysiology as it has been demonstrated to be significantly elevated during the development of AP, and the level was reported to be associated with the severity of AP [113]. Several studies have shown promising results in the early prediction of severe AP [114].…”
Section: Interleukin-8mentioning
confidence: 99%
“…Further studies have also highlighted that both pancreatitis and IBD share a common immune dysregulation and an altered cytokines expression, such as an abnormal elevation of IL-1β, IL-6, IL-8, and IL-10, thus supporting the susceptibility for IBD patients to develop pancreatic manifestations over time [ 42 , 43 , 44 ].…”
Section: Role Of Genetics In Pediatric Pancreatitis and Its Association With Ibdmentioning
confidence: 99%